Development and testing of new anode efficiency system for sacrificial anode - Mohd Redzwan Rosli (Universiti Malaysia Perlis, 2008)
Magnesium based alloy is the most suitable material as sacrificial anodes for corrosion control in underground environment. Performance of control corrosion by anode was depend on efficiency to protect cathode from corrode. Develop of the new system for determines efficiency of anode. The systems are combination between of impressed current and sacrificial concept. Single and triple corrosion cell its 2 new system, where the both it different design. Single corrosion cell was use a container, thus this system must be test repeated at least 3 range values at 1 type of specimen. The efficiency and actual current capacity value of PMg using single corrosion cell is 48.48% and 1069.83 Ah/kg respectively. For triple corrosion cell it use 3 containers, thus advantage this system is the reduce time consuming testing because requires only a tested for a type of specimen. The efficiency and actual current capacity value of HPMg using triple corrosion cell is 55.11% and 1215.928Ah/kg respectively. Methods system, current flow, electrolyte resistivity and specimen preparation are the influencing for evaluate the efficiency of anode. The value of efficiency will be changing when the effect exist in efficiency testing of anode. Circuit open potential was the additional system to evaluate of anode performance. This system to measure potential value exists in connection between anode specimen and saturated calomel reference electrode. The potential of electronegative value for HPMg higher than PMg was -1740mV. The other hand pitting dept for HPMg lower than PMg was 127um. It cause expects life of HPMg was long.